1981
DOI: 10.1128/iai.31.3.906-910.1981
|View full text |Cite
|
Sign up to set email alerts
|

Development of immunity to porcine rotavirus in piglets protected from disease by bovine colostrum

Abstract: Bovine colostrum with rotavirus-neutralizing activity was fed for 10 days to two groups of piglets, one of which was inoculated intranasally with a rotavirus of porcine origin. A third group, which did not receive colostrum, was also inoculated with the virus, and these piglets developed diarrhea, excreted rotavirus in the feces, and died 6 days after infection. In contrast, the infected piglets fed with bovine colostrum remained healthy, although they developed antibody to rotavirus. Twenty-seven days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
5
13
0
Order By: Relevance
“…The active immunity was indicated by a transient increase of blood serum IgA and IgM antibody following virus challenge. Observations were similar in studies of passive immunity in rotavirus-challenged gnotobiotic lambs fed homologous colostrum (67) or gnotobiotic piglets fed bovine colostrum (9). As further illustrated in Figure 6 for CD #54 calf, calves had high serum IgG1 and virus neutralizing antibody titers after 2 i.m.…”
Section: Passive Immunity Against Type 1 Viruses: Lactogenic Immunitysupporting
confidence: 72%
See 2 more Smart Citations
“…The active immunity was indicated by a transient increase of blood serum IgA and IgM antibody following virus challenge. Observations were similar in studies of passive immunity in rotavirus-challenged gnotobiotic lambs fed homologous colostrum (67) or gnotobiotic piglets fed bovine colostrum (9). As further illustrated in Figure 6 for CD #54 calf, calves had high serum IgG1 and virus neutralizing antibody titers after 2 i.m.…”
Section: Passive Immunity Against Type 1 Viruses: Lactogenic Immunitysupporting
confidence: 72%
“…Depending on a number of poorly understood variables, calves then may begin shedding rotavirus with or without accompanying disease. The present investigation and others (9,67) indicate that whereas most animals that are protected while receiving passive immunity may develop active immunity, other animals may remain susceptible to a subsequent infection, becoming a source of virus for additional animals. This might explain partially the occasional occurrence of sequential rotavirus infections in the same animal.…”
Section: Passive Immunity Against Type 1 Viruses: Lactogenic Immunitysupporting
confidence: 53%
See 1 more Smart Citation
“…A similar survey carried out on children found that rotavirus shedding was detected to the same degree in children with or without diarrhoea (Barron-Romero et al, 1985). The reasons for sub-clinical reactions to infection have not been fully elucidated, but there is experimental evidence that oral administration of antibody during virulent rotavirus infection eliminates any clinical signs of the infection (Snodgrass and Wells, 1976;Bridger and Brown, 1981). Differences in virulence among bovine rotaviruses have also been reported (Carpio et al, 1981) but naturally occurring avirulent strains have not yet been isolated and characterised.…”
Section: Introductionmentioning
confidence: 98%
“…The supportive properties of BC when consumed by other mammalian species, including pigs and humans, are well documented in the medical literature (Bridger and Brown, 1981;Pakkanen and Aalto, 1997;Gopal and Gill, 2000;He et al, 2001;Solomons, 2002;Uruakpa et al, 2002;Boudry et al, 2007;Struff and Sprotte, 2007). Emerging evidence indicates that BC is a promising nutraceutical that could prevent or mitigate various diseases in newborns and adults (Bagwe et al, 2015), in particular gastrointestinal infections.…”
Section: Discussionmentioning
confidence: 99%